Decoding the genome and epigenome of avian Escherichia coli strains by R10.4.1 nanopore sequencing - Wang, Jingyao; Liu, Xudong; Shao, Yanwen; Li, Runsheng; Paudel, Surya (Frontiers in Veterinary Science, 2025)
Avian pathogenic Escherichia coli (APEC) causes colibacillosis in poultry, which is a very important disease worldwide. Despite well-documented genomic traits and diversity of APEC, its epigenomic characteristics are less understood. This study utilized the high throughput and long-read capabilities of Oxford Nanopore Technology (ONT) to elucidate the genome structures and methylation modifications of three E. coli isolates of avian origin: one intestinal isolate from a healthy wild bird and two systemic isolates from clinically affected chickens. Three complete genomes, each comprising a single chromosome and multiple plasmids were assembled. Diverse virulence-associated genes, antimicrobial resistance genes, mobile genetic elements plasmids and integrons were characterized from the genomes. Despite a limited sample size, our whole genome sequencing (WGS) data highlighted significant genomic diversity among the E. coli strains and enriched repertoire of gene clusters related to APEC pathogenicity. From the epigenetic analysis, multiple methylation modifications, including three N5-methylcytosine (5mC), eight N6-methyladenine (6mA) and two N4-methylcytosine (4mC) modification motifs were identified within all three isolates. Furthermore, common GATC and CCWGG methylation motifs were predominantly distributed within regulatory regions, suggesting a role in epigenetic transcription regulation. This study opens the avenue for future research into pathogenesis, diagnostic and therapeutic strategies of APEC considering epigenetic analysis.